PENGARUH STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA UD. DESTA JAYA HILISIMAETANO - Mihaena Dachi (Universitas Nias Raya, 2022)
This study aims to determine the effect of job satisfaction and work motivation on employee performance at the Kantor Camat Lahusa. This type of research is a quantitative associative research. The sample in this study amounted to 32 employee. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that jon satisfaction (X1) and Work Motivation (X2) have a positive and significant effect on employee performance (Y) at the Lahusa district office with a t value for job satisfaction (X1) of 2,793 > t table 1,697 and significant level of 0,009 < 0,05 and for the work motivation variable (X2) obtained t value of 2,282 > t table 1,697 and signifikan level of 0,030 < 0,05, then the decision was Ha accepted H0 is rejected with the meaning that Job Satisfaction (X1) and Work Motivation (X2) has an effect on the Employee Performance variable (Y) at the Lahusa District Office.